The characterisation of N-Acetyltransferase (NAT) in Mycobacterium tuberculosis - Sholto-Douglas-Vernon, Carolyn (Stellenbosch : University of Stellenbosch, 2010)
Thesis (PhD (Molecular Biology and Human Genetics))--University of Stellenbosch, 2005.